Design and development of secure device association and communication in wireless body area networks - Loke, Lup Peng. (2013)
Wireless Sensor Networks (WSNs) consist of distributed sensor nodes that monitor specific environmental variables and transmit data back to a central node for further processing. One type of WSN is the Wireless Body Area Network (WBAN), which comprises of several wearable physiological sensor nodes distributed across the body and a central unit that manages them.